Vocabulary acquisition and the use of dictionaries portuguese-english - Polizer, Alex Sandro da Silva [UNESP]; Marques, Giseli Sampaio de Oliveira [UNESP]; Zacarias, Regiani Aparecida Santos [UNESP] (Federal Univ Ceara, 2022)
This article deals with the teaching of vocabulary with the Portuguese/ English dictionary. It highlights the importance of the effective use of a new word/ expression in order to guarantee language acquisition. The theoretical reference relies on Alves (1988), Biderman (1996, 1998), Jacobs (2002), Krieger (2006), Zacarias (2011), Lima (2014) and Fragoso (2018). The objective is to provide opportunities to expand the lexical repertoire of English in the school context by means of dictionary use. This work also presents a didactic sequence of activities for teaching vocabulary using the dictionary as source material. The activity is divided into three moments, the first one is aimed at arising students interest by their prior knowledge; the second, consists of presenting to students the parts of the dictionaries, and also its content and how the information is conveyed -as example in the Longman dictionary; the third moment brings suggestions to help students use new vocabulary effectively, such as word lists for easy reviews and personal consultations. The article also offers new perspectives regarding pedagogical lexicography. It is expected to collaborate and promote the effective use of Portuguese/English dictionaries in the classroom and to motivate their use in the extra-class environment, so as to encourage continuous and autonomous learning. Likewise, it is expected to contribute to some reflection on the improvement of lexicographic works from the perspective of the learner.
Keywords: Pedagogical Lexicography; Dictionary; Vocabulary